Semi-automatic dough weighing machine for enhanced productivity in quality control processes - Abd Rahim, Nuranisa Suhada; Yang, Chuan Choong; Zulkarnain, Nur Dalilah; Mohamad Hanif, Noor Hazrin Hany (IEEE, 2024)
In the process of making bread, dough development is a critical process to ensure the final quality of the bread. Dividing and weighing the dough to achieve the correct weight for the desired bread type and quality is one of the critical processes in dough development. Currently, small-scale bakeries still apply manual weighing method, which affects the productivity of the bakery. This is because manual weighing process is tedious and consumes lots of time. Thus, in this work, a semi-automatic machine that is capable to control the weight quality of dough is proposed to improve productivity. The proposed machine can weigh and sort the dough according to their weight specification. Experimental test was conducted by collecting the coordinate of the final location of dropped dough by varying the parameters of speed of motor and height of the space between lower platform of weight checker and bottom of machine. From the output data obtained, the optimum speed of the motor was 50 rpm and the optimum height of space between lower platform and bottom of machine was 100 mm. From the experimental test, it indicates that speed of motor and height of the machine directly affects how the machine is operating and influencing the outcome of the work. Therefore, a novel workflow to design and develop a dough weighing machine using gravity concept to improve productivity was achieved.